Endovascular stent-graft applications in latrogenic vascular injuries - (:unkn) unknown (My University, 2003)
PURPOSE: To report the results of covered stent applications in iatrogenic vascular injuries. METHODS: We report 17 patients (11 men, 6 women; age range 20-59 years, mean age 40 years) who underwent repair of different iatrogenic vascular lesions by means of endovascular covered stents. The patient population consisted of 8 femoral arteriovenous fistulae, 4 common femoral artery pseudoaneurysms, 1 subclavian artery pseudoaneurysm, 1 abdominal aortic aneurysm, 1 iliac artery perforation, 2 porto-biliary fistulae that developed during TIPS procedure. Balloon-expandable stent-grafts were used in all patients except one. Control studies were performed with angiography. RESULTS: Technical success was achieved in all 17 patients. The mean clinical follow-up period for all 17 patients was 8 months. There were no signs of stent migration or leaks in the control studies. Only one patient developed a hemodynamically insignificant stenosis at the proximal end of the stent. There have been no stent deformations or related complications during the follow-up period. CONCLUSION: Our short-term results suggest that endovascular treatment is a low-risk procedure and appears less invasive than surgery for the treatment of different types of iatrogenic vascular injuries. Intermediate and long-term results are not available.
Keywords: Adult; Female; Humans; Middle Aged; Treatment Outcome; Male; Stents; Vascular Diseases; Catheterization; Iatrogenic Disease